Tumor-To-Tumor Metastasis of Poorly Differentiated Gastric Carcinoma to Uterine Lipoleiomyoma - Ryo Kiyokoba; Hiroshi Yagi; Hideaki Yahata; Yoshiaki Kawano; Eisuke Kaneki; Kaoru Okugawa; Kenzo Sonoda; Kiyoko Kato (Case Reports in Obstetrics and Gynecology)
The rare phenomenon of tumor-to-tumor metastasis was first described in 1930. The donor neoplasm is most frequently lung or breast carcinoma, whereas intracranial meningiomas are reportedly the commonest recipient neoplasm. Here we report a case of metastasis from a primary gastric cancer to a uterine lipoleiomyoma. A 65-year-old woman presented with locally advanced gastric cancer with computed tomography (CT) evidence of peritoneal dissemination and a 9 cm pelvic mass. She underwent 16 courses of TS-1/cisplatin chemotherapy, which achieved significant tumor reduction. However, repeat CT and magnetic resonance imaging revealed a 9 cm diameter pelvic mass adjacent to the uterus. The mass was heterogeneously hyperintense on T1- and T2-weighted images with some low signal spots on fat-suppressed T1-weighted images, suggesting a benign ovarian tumor such as a mature cystic teratoma. After 3 months, pelvic CT revealed a 10 cm multilocular cystic mass that exhibited heterogeneous enhancement after intravenous contrast administration. A diagnostic laparotomy revealed a subserosal uterine tumor extending into the right broad ligament; total abdominal hysterectomy and bilateral salpingo-oophorectomy was performed. The uterine tumor showed histological features of lipoleiomyoma infiltrated by well- to moderately differentiated carcinoma cells that were similar to those of the gastric biopsy, supporting a diagnosis of metastatic gastric adenocarcinoma.